2017
DOI: 10.4152/pea.201704233
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Anti-Corrosion Properties of Novel Quinolinol on C-steel in a Molar Hydrochloric Acid Solution

Abstract: New quinoline, namely 5-(ethoxymethyl)-8-quinolinol (M-QN), has been synthesized and characterized by different spectral methods, such as 1 H NMR, <13 C NMR and IR spectra. Its inhibitive action against the corrosion of carbon steel in 1.0 M hydrochloric acid solution was investigated at different temperatures in the range from 25±2 to 55±2 °C by a series of known techniques, such as weight loss, open circuit potential (OCP), electrochemical impedance spectroscopy (EIS) and Tafel polarization measurements. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In the inhibitors presence, both anodic and cathodic Tafel slopes remained almost unchanged ( Fig. 2), indicating that the inhibitors acted by merely blocking the reaction sites of the metal surface, without changing the anodic and cathodic reaction mechanisms [25]. Furthermore, even in the inhibitor presence, it was observed that the corrosion rate increased at more positive potentials to ~ -0.250 V, and that the mechanism of anodic dissolution reaction changed.…”
Section: Potentiodynamic Polarizationmentioning
confidence: 93%
See 2 more Smart Citations
“…In the inhibitors presence, both anodic and cathodic Tafel slopes remained almost unchanged ( Fig. 2), indicating that the inhibitors acted by merely blocking the reaction sites of the metal surface, without changing the anodic and cathodic reaction mechanisms [25]. Furthermore, even in the inhibitor presence, it was observed that the corrosion rate increased at more positive potentials to ~ -0.250 V, and that the mechanism of anodic dissolution reaction changed.…”
Section: Potentiodynamic Polarizationmentioning
confidence: 93%
“…The calculation parameters used in the geometry optimization for the T3-Fewater system. For the whole simulation procedure, the COMPASS (Condensed-phase Optimized Molecular Potentials for Atomistic Simulation Studies) force field [25] was used to optimize the structures of all the system's components. COMPASS is the first ab-initio force field that enables accurate and simultaneous prediction of chemical properties (structural, vibrational, conformational, etc.)…”
Section: Molecular Dynamics Simulations; Adsorption Energy Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation shows that the activation controls hydrogen evolution, and the presence of inhibitor does not change the mechanism of the cathodic evolution reaction [28][29] . From Table 4, the inhibition efficiency increased with decreasing the concentration of S1 and this inhibitor affect the cathodic and anodic inhibition through adsorption on the working electrode surface by blockage of the active sites 30 . The corrosion potential Change slightly.…”
Section: Polarization Curvesmentioning
confidence: 94%
“…heteroatoms such as oxygen (O), nitrogen (N), phosphorus (P), sulfur (S); 2. aromatic component having multiple bonds leading to easier adsorption on the metal surface; 3. functional groups such as = NH, -CHO, -C≡N, -N = N-…; 4. heterocyclic compounds such as imidazole, quinoline, quinoxaline, phenyltetrazole, etc. [6,7].…”
Section: Introductionmentioning
confidence: 99%